Anti-oxidative Amino Acid L-ergothioneine Modulates the Tumor Microenvironment to Facilitate Adjuvant Vaccine Immunotherapy - Yoshida, Sumito; Shime, Hiroaki; Matsumoto, Misako; Kasahara, Masanori; Seya, Tsukasa (Frontiers in Immunology, 2019)
Cancer vaccines consist of a tumor-associated antigen (TAA) and adjuvant. These vaccines induce and activate proliferation of TAA-specific cytotoxic T lymphocytes (CTLs), suppressing tumor growth. The therapeutic efficacy of TAA-specific CTLs depends on the properties of tumor microenvironment. The environments make immunosuppressive by function of regulatory T cells and tumor-associated myeloid cells; thus, regulation of these cells is important for successful cancer immunotherapy. We report here that L-ergothioneine (EGT) with the adjuvant Toll-like receptor 2 (TLR2) ligand modulated suppressive microenvironments to be immune-enhancing. EGT did not augment DC-mediated CTL priming or affect CTL activation in draining lymph node and spleen. However, EGT decreased the immuno-suppressive function of tumor-associated macrophages (TAMs). TLR2 stimulation accompanied with EGT administration downregulated expression of PD-L1, CSF-1R, arginase-1, FAS ligand, and TRAIL in TAMs, reflecting reduction of CTL suppression. An anti-oxidative thiol-thione residue of EGT was essential to dampening CTL suppression. The effect was specific to the thiol-thione residue of EGT because no effect was observed with another anti-oxidant N-acetyl-L-cysteine. A CTL-suppressive environment made by TLR2 is relieved to be improved by the addition of EGT, which may ameliorate the efficacy of vaccine immunotherapy.